Research on methanol-tolerant catalysts for the oxygen reduction reaction - Asteazaran, Mariano (2015)
Direct methanol fuel cells (DMFCs) generate electricity in a clean and efficient way, so they are a valuable alternative to traditional environmentally harmful technologies. Portable power sources are one of the applications of passive DMFCs. One of the requirements in these devices is the use of high alcohol concentration. Methanol permeation across the polymer electrolyte membrane (methanol crossover) causes a loss of fuel cell efficiency as the oxygen reduction reaction (ORR) and the methanol oxidation reaction (MOR) occur simultaneously at the cathode. To develop methanol-tolerant catalysts with suitable activity, different PtM/C and PtMRu/C combinations with M = Co or Fe were prepared by a modified impregnation method. The synthesized catalysts were studied to determine the role of the components in enhancing the ORR and simultaneously discouraging the MOR. The materials were characterized by TEM, XPS and EDS. Well-distributed particles for all the catalysts were shown by TEM. XPS spectra revealed that the method produces a great amount of metallic Pt. The electrochemical characterization was carried out by linear sweep voltammetry and cyclic voltammetry, in a three-electrode electrochemical cell with a glassy carbon rotating disk electrode covered with a thin catalytic layer and a Nafion® film as the working electrode. Binary and ternary catalysts have a good activity for the ORR. However, the enhanced activity of binary catalysts is lost when the ORR is studied in the presence of methanol. Ternary catalysts containing Ru showed higher methanol-tolerance, regardless of the composition.